2014
DOI: 10.3389/fmars.2014.00068
|View full text |Cite
|
Sign up to set email alerts
|

Large centric diatoms allocate more cellular nitrogen to photosynthesis to counter slower RUBISCO turnover rates

Abstract: Diatoms contribute ∼40% of primary production in the modern ocean and encompass the largest cell size range of any phytoplankton group. Diatom cell size influences their nutrient uptake, photosynthetic light capture, carbon export efficiency, and growth responses to increasing pCO 2 . We therefore examined nitrogen resource allocations to the key protein complexes mediating photosynthesis across six marine centric diatoms, spanning 5 orders of magnitude in cell volume, under past, current and predicted future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…The prevalence of larger phytoplankton cells in eutrophic and brackish coastal waters can be explained by enhanced resistance to predation (Ward et al 2012), greater nutrient storage capacity (Grover 2011) and potentially lower metabolic costs to withstand and exploit fluctuating light because of lower susceptibility to photoinactivation of PSII (Key et al 2010). We found that under near-saturating growth light and media with high-nitrogen larger diatoms invested more cellular nitrogen to RUBISCO than did smaller ones, to counter a lower achieved RUBISCO turnover rate (Wu et al 2014b), a finding that parallels increased allocations to RUBISCO in cold water diatoms where RUBISCO performance is kinetically limited (Losh et al 2013; Young et al 2015). To explain our finding of slower achieved RUBISCO turnover in larger diatoms (Wu et al 2014b), we hypothesized that in higher-nitrogen (HN) media large cells have luxury accumulation of RUBISCO protein that in turn lowers their achieved performance per unit RUBISCO.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The prevalence of larger phytoplankton cells in eutrophic and brackish coastal waters can be explained by enhanced resistance to predation (Ward et al 2012), greater nutrient storage capacity (Grover 2011) and potentially lower metabolic costs to withstand and exploit fluctuating light because of lower susceptibility to photoinactivation of PSII (Key et al 2010). We found that under near-saturating growth light and media with high-nitrogen larger diatoms invested more cellular nitrogen to RUBISCO than did smaller ones, to counter a lower achieved RUBISCO turnover rate (Wu et al 2014b), a finding that parallels increased allocations to RUBISCO in cold water diatoms where RUBISCO performance is kinetically limited (Losh et al 2013; Young et al 2015). To explain our finding of slower achieved RUBISCO turnover in larger diatoms (Wu et al 2014b), we hypothesized that in higher-nitrogen (HN) media large cells have luxury accumulation of RUBISCO protein that in turn lowers their achieved performance per unit RUBISCO.…”
Section: Introductionmentioning
confidence: 98%
“…We found that under near-saturating growth light and media with high-nitrogen larger diatoms invested more cellular nitrogen to RUBISCO than did smaller ones, to counter a lower achieved RUBISCO turnover rate (Wu et al 2014b), a finding that parallels increased allocations to RUBISCO in cold water diatoms where RUBISCO performance is kinetically limited (Losh et al 2013; Young et al 2015). To explain our finding of slower achieved RUBISCO turnover in larger diatoms (Wu et al 2014b), we hypothesized that in higher-nitrogen (HN) media large cells have luxury accumulation of RUBISCO protein that in turn lowers their achieved performance per unit RUBISCO. To test this hypothesis, we grew two representative diatom strains with a ~4 orders of magnitude difference in cell biovolume, small Thalassiosira pseudonana (~40 µm 3 ) and large T. punctigera (~300,000 µm 3 ) in turbidostats across a range of growth light, in lower-nitrogen (LN) media to attempt to limit cellular luxury accumulation of RUBISCO protein, compared with cells grown in a typical laboratory HN media.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the set of culture species compiled here major taxonomic groups are underrepresented. For example, diatoms usually have higher P:C than other groups (Quigg et al, 2003) or larger diatom species invest a much greater fraction of their N pool into Rubisco than smaller species (Wu et al, 2014). To describe these trends, also model coefficients in Table S2 may be more group specificor should vary at time-scales larger than the few weeks considered…”
Section: Scaling Up To Real Ecosystemsmentioning
confidence: 99%